Determining voltage stability margin values by measuring the hypotenuse under PV and QV curves - Mohamad Nor, Ahmad Fateh; Sulaiman, Marizan; Abdul Kadir, Aida Fazliana; Omar, Rosli (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2018)
Voltage instability is one of the main causes of electrical power system blackouts all around the world. Voltage instability can be analyzed with the used of PV and QV curves technique. From these curves, the values of voltage stability margin (VSM) can be determined. VSM is very important in analyzing voltage instability because it shows the distance of how far the power system is able to run before experiencing voltage instability. This paper presents the calculation of VSM values by measuring the hypothenuse under the PV and QV curves. These VSM values are used to determine the weakest bus in the power system. Then, these values are compared with the VSM values that are being calculated using the conventional equation. The IEEE 14-bus power system has been chosen as the reference electrical power system.